Correction to what drives the redox properties of model green fluorescence protein chromophores? - Solntsev, Kyril M.; Ghosh, Debashree; Amador, Adrian; Josowicz, Mira; Krylov, Anna I. (Journal of Physical Chemistry Letters, 2011)
We report the first experimental determination of the oxidation potentials E-ox(0). (relative to the standard hydrogen electrode, SHE) of model green fluorescent protein (GFP) chromophores. Para-, meta, and ortho-hydroxy (4-hydroxybenzylidene-2,3-dimethylimidazolinone, HBDI) and methoxy (MeOBDI) derivatives were studied. E-ox(0) of the three isomers in acetonitrile are -1.31, -1.52, and -1.39 V, respectively. Electronic structure calculations reproduce the observed differences between the isomers and reveal that E-ox(0) follows the ionization energies (IEs), that is, p-MeOBDI has the lowest IE (6.96 eV in the gas phase) due to resonance stabilization of its cation, whereas the resonance is detuned in m-MeOBDL resulting in more-negative E-ox(0). The observed meta and ortho effects in E-ox(0) are similar to the trends in pK(a). The effect of increased solvent polarity on absolute.E-ox(0) (and especially on para-meta-ortho differences) was found to be small. The redox properties of GFP chromophores are driven by their structure and can be correlated with IEs, which can be exploited in predicting the properties of other fluorescent protein chromophores.

What drives the redox properties of model green fluorescence protein chromophores? - Solntsev, Kyril M.; Ghosh, Debashree; Amador, Adrian; Josowicz, Mira; Krylov, Anna I. (Journal of Physical Chemistry Letters, 2011)
We report the first experimental determination of the oxidation potentials E-ox(0). (relative to the standard hydrogen electrode, SHE) of model green fluorescent protein (GFP) chromophores. Para-, meta, and ortho-hydroxy (4-hydroxybenzylidene-2,3-dimethylimidazolinone, HBDI) and methoxy (MeOBDI) derivatives were studied. E-ox(0) of the three isomers in acetonitrile are -1.31, -1.52, and -1.39 V, respectively. Electronic structure calculations reproduce the observed differences between the isomers and reveal that E-ox(0) follows the ionization energies (IEs), that is, p-MeOBDI has the lowest IE (6.96 eV in the gas phase) due to resonance stabilization of its cation, whereas the resonance is detuned in m-MeOBDL resulting in more-negative E-ox(0). The observed meta and ortho effects in E-ox(0) are similar to the trends in pK(a). The effect of increased solvent polarity on absolute.E-ox(0) (and especially on para-meta-ortho differences) was found to be small. The redox properties of GFP chromophores are driven by their structure and can be correlated with IEs, which can be exploited in predicting the properties of other fluorescent protein chromophores.

Effects of the benzoxazole group on green fluorescent protein chromophore crystal structure and solid state photophysics - Ghodbane, Abdelhamid; Fellows, W. Brett; Bright, John R.; Ghosh, Debashree; Saffon, Nathalie; Tolbert, Laren M.; Fery-Forgues, Suzanne; Solntsev, Kyril M. (Journal of Materials Chemistry C, 2016)
Four benzoxazole-substituted GFP chromophores that differ by the length of their alkyl chain (from C1 to C12) were synthesized. In solution, the four compounds showed identical spectroscopic behavior, emitting blue light with moderate quantum yield. In the solid state, the butyl, pentyl and dodecyl derivatives strongly emitted orange light, while the methyl derivative was only weakly emissive. Based on the X-ray data and DFT calculations, emission in the solid state was explained by the formation of excimers. A very unusual ``hot-dog''-type excimer was found for the dodecyl derivative, in which two overlapping chromophores are separated by an alkyl chain.